2000
DOI: 10.1097/00004691-200003000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Neuromagnetic Recordings in Temporal Lobe Epilepsy

Abstract: The introduction of whole-head magnetoencephalography (MEG) systems facilitating simultaneous recording from the entire brain surface has established MEG as a clinically feasible method for the evaluation of patients with temporal lobe epilepsy (TLE). In mesial TLE, two types of MEG spike dipoles could be identified: an anterior vertical and an anterior horizontal dipole. Dipole orientations can be used to attribute spike activity to temporal lobe subcompartments. Whereas the anterior vertical dipole is compat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
88
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 44 publications
7
88
1
2
Order By: Relevance
“…The perilesional irritable area was successfully localized by MEG in our patients with neocortical lesion, as found previously (20). Additionally, we found extensive spike localization in two patients.…”
Section: Figsupporting
confidence: 87%
See 3 more Smart Citations
“…The perilesional irritable area was successfully localized by MEG in our patients with neocortical lesion, as found previously (20). Additionally, we found extensive spike localization in two patients.…”
Section: Figsupporting
confidence: 87%
“…Classification of temporal lobe MEG spikes into anterior temporal horizontal (ATH), anterior temporal vertical (ATV), and posterior temporal vertical (PTV) dipoles (18,19) and comparison with ECoG findings showed that dominant ATH and ATV dipoles were correlated with seizure onset from the medial temporal structures, whereas PTV dipoles were correlated with onset from the lateral temporal neocortex or nonlocalized onset. Investigation of the relation between the dipole pattern and clinical diagnosis found that patients with medial TLE showed ATH or ATV dipoles, whereas patients with nonlesional TLE (no MRI abnormalities) showed dipoles localized on the anterior medial or posterior lateral temporal lobe (20). In the present study, all five patients with…”
Section: Correlation Between Postoperative Seizure Outcome and Magnetsupporting
confidence: 42%
See 2 more Smart Citations
“…Depth electrode recordings and lesion studies in epilepsy patients have shown that deep temporomesial structures like the hippocampus (HC) are important for the pathophysiology of epileptogenesis. However, depth electrode recordings show that with conventional dipole localization approaches activity originating from deep brain structures is likely to escape detection [2]. To noninvasively elucidate time course and location of these sources during epileptiform discharges we used a localization approach based on spatial filtering taking into account the spatio-temporal information of the measured MEG signal.…”
mentioning
confidence: 99%